Chasing Augustus - Fusco, Kimberly Newton (New York : Alfred A. Knopf, an imprint of Random House Children's Books, 2017)
During a rough year in which she was placed in the care of her prickly grandfather after her father suffered a stroke, Rosie embarks on a search for her missing dog after he is given away by her estranged mother.
"A Borzoi book."
Keywords: Dogs -- Juvenile fiction; Lost articles -- Juvenile fiction; Families -- Juvenile fiction; Grandfathers -- Juvenile fiction; Dogs -- Fiction; Lost and found possessions -- Fiction; Family problems -- Fiction; Grandfathers -- Fiction; Family problems -- Fiction; Lost and found possessions -- Fiction; Grandfathers -- Fiction; Dogs -- Fiction